Who Drinks Where: Youth Selection of Drinking Contexts. (17th March 2015) - Lipperman‐Kreda, Sharon; Mair, Christina F.; Bersamin, Melina; Gruenewald, Paul J.; Grube, Joel W.
<x xml:space="preserve">Abstract</x> Background Different drinkers may experience specific risks depending on where they consume alcohol. This longitudinal study examined drinking patterns, and demographic and psychosocial characteristics associated with youth drinking in different contexts. Methods We used survey data from 665 past‐year alcohol‐using youths (ages 13 to 16 at Wave 1) in 50 midsized California cities. Measures of drinking behaviors and drinking in 7 contexts were obtained at 3 annual time points. Other characteristics included gender, age, race, parental education, weekly disposable income, general deviance, and past‐year cigarette smoking. Results Results of multilevel regression analyses show that more frequent past‐year alcohol use was associated with an increased likelihood of drinking at parties and at someone else's home. Greater continued volumes of alcohol (i.e., heavier drinking) was associated with increased likelihood of drinking at parking lots or street corners. Deviance was positively associated with drinking in most contexts, and past‐year cigarette smoking was positively associated with drinking at beaches or parks and someone else's home. Age and deviance were positively associated with drinking in a greater number of contexts. The likelihood of youth drinking at parties and someone else's home increased over time, whereas the likelihood of drinking at parking lots/street corners decreased. Also, deviant youths progress to drinking in their own home, beaches or parks, and restaurants/bars/nightclubs more rapidly. Conclusions The contexts in which youths consume alcohol change over time. These changes vary by individual characteristics. The redistribution of drinking contexts over the early life course may contribute to specific risks associated with different drinking contexts.